Cultivation of Paddy straw Mushrooms (Volvariella volvacea, ) in the Lateritic Zone of West Bengal-A Healthy food for Rural People - M. K. Biswas (International Journal of Economic Plants)
Paddy straw mushroom (Volvariella spp.) also called ‘straw mushroom’ is a fungus of the tropics and subtropics and has been cultivated for many years in India . This mushroom has several advantages like requirement of the tropical or sub-tropical climate, fast growth rate, easy cultivation technology and good acceptability at consumers’ level. Paddy straw mushroom contains good amount of protein, crude fibres and ash, all make it a health diet along with superior composition of various elements and essential amino acids. West Bengal has tremendous potential of commercial cultivation of Volvariella volvacea due to the easy availability of paddy straw and good environmental conditions. This mushroom can easily be grown by the rural women which not only generate income for them but also helpful for meeting their daily protein requirements. An investigation was carried out at a mushroom farm of Bolpur, Birbhum ,W.B. during the season 2008-2010 to find out the suitability of cultivation of this mushroom under the agro-ecological condition of red and lateritic belt of West Bengal. Varous substrates i.e. paddy straw, paddy straw+Wheat straw 1:1 , banana leaf+paddy straw 1:1 , water hyacinth+paddy straw 1:1 , mustard straw+paddy straw 1:1 and maize straw+paddy straw 1:1 were taken to find out their suitability for cultivation of Volvariella volvacea. Different methods of cultivation i.e. bed method ,cage method ,spiral method and heap method were further tried to identify a suitable method of cultivation for the locality. Paddy straw was found to be most appropriate substrate in terms of yield and biological efficiency followed by maize straw+paddy straw 1:1 and banana leaf+paddy straw 1:1 which were exhibited 10.20, 9.8 and 8.5% biological efficiency respectively.While, mustard straw+paddy straw 1:1 substrate was found unsuitable for paddy straw mushroom cultivation.Among the various methods of cultivation,bed method of cultivation has showed its supremacy among all the treatments. The information will help the farmers for decision making for diversifying their cultivation as well generating extra income.